2002
DOI: 10.1097/00006231-200205000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and washout of 99mTcV-dimercaptosuccinic acid and 99mTc-sestamibi in the assessment of histological type and grade in breast cancer

Abstract: This study was performed to investigate the relationship between histological type and grade, with the uptake and washout of 99mTc-hexakis-2-methoxyisobutylisonitrile (99mTc-sestamibi, 99mTc-MIBI) and 99mTcV-dimercaptosuccinic acid (99mTcV-DMSA) in breast cancer. Forty-five patients with histologically proven breast cancer had previously been referred for 99mTcV-DMSA and/or 99mTc-MIBI scintimammography. Twenty-five of them underwent both 99mTcV-DMSA and 99mTc-MIBI scintigraphy in a double phase study. Lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Denoyer and colleagues recently reported that the radiotracer uptake is specifically mediated by NaPi cotransporter type III in cancer cells, similar to phosphate ions, which enter cells via NaPi cotransporters [13], while other reports suggest that its uptake in tumors is related to glucose metabolism-mediated acidosis [14]. 99m Tc-(V)DMSA has been tried out in identifying invasive and preinvasive breast cancer [15-17]. …”
Section: Introductionmentioning
confidence: 99%
“…Denoyer and colleagues recently reported that the radiotracer uptake is specifically mediated by NaPi cotransporter type III in cancer cells, similar to phosphate ions, which enter cells via NaPi cotransporters [13], while other reports suggest that its uptake in tumors is related to glucose metabolism-mediated acidosis [14]. 99m Tc-(V)DMSA has been tried out in identifying invasive and preinvasive breast cancer [15-17]. …”
Section: Introductionmentioning
confidence: 99%
“…99m Tc(V)-DMSA is a well-known tumor-seeking radiotracer with affinity for neuroendocrine and soft tissue tumors, such as medullary thyroid carcinoma and lung, breast, brain, and metastatic bone lesions [Ohta et al, 1984, Babbar et al, 1991, Kashyap et al, 1992, Hirano et al, 1995, Atasever et al, 1997, Lam et al, 1997, Kiratli et al, 1998, Papantoniou et al, 2002, 2010, Denoyer et al, 2004, Tsiouris et al, 2007, Al-Saeedi, 2007. These tumor-seeking properties have lead to the use of 99m Tc(V)-DMSA in scintimammographic studies.…”
Section: M Tc(v)-dmsa Scintimammographymentioning
confidence: 99%
“…Regarding lymph node involvement, the tracers have been reported to show 78.9% sensitivity and 86.3% specificity. Pre-invasive lesions, like DCIS and lobular carcinoma in situ (LCIS) are detected with high sensitivity by 99m Tc(V)-DMSA, whereas with high specificity by 99m Tc-sestamibi [Papantoniou et al, 2001[Papantoniou et al, , 2002.…”
Section: M Tc(v)-dmsa Scintimammographymentioning
confidence: 99%
See 1 more Smart Citation
“…Papantoniou et al evaluated the relationship between the histological type and grade of the tumor and the uptake and washout of 99m Tc-sestamibi. They found that the 99m Tc-sestamibi uptake ratios were significantly higher in ductal than in lobular carcinomas [20]. Furthermore, grade II carcinomas also showed a significantly faster washout (i. e., lower retention index values) than that observed in grade III tumors [20].…”
Section: Introductionmentioning
confidence: 99%